2007
DOI: 10.1038/sj.leu.2404567
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2 V617F mutation is detectable in granulocyte populations at greater than two copies per cell among individuals with myeloproliferative disorders

Abstract: Huang et al. used an allele-specific PCR 6-8 followed by separation and detection with capillary electrophoresis and this test has a sensitivity up to 200 pg mutated DNA; they only sequenced selected cases. The method used has the same sensitivity as our method (allele-specific pcr), but the result is displayed by capillary electrophoresis instead of agarose gel electrophoresis.This study confirms our previous report 4 bringing out the absence of a significant involvement of JAK2 V617F mutation in the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Patients with GC DLBCL have been shown to exhibit a more favorable clinical outcome than patients with non-GC DLBCL. 1 As with cDNA microarray, immunohistochemistry can also be used to distinguish the GC/non-GC subtype of DLBCL and to predict survival, 2 but there have been few reports comparing clinical outcomes in cases of GC DLBCL and non-GC DLBCL treated with rituximab. 3,4 We retrospectively analyzed the treatment effect of rituximab with conventional chemotherapy on these two DLBCL subtypes by means of immunohistochemistry.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Patients with GC DLBCL have been shown to exhibit a more favorable clinical outcome than patients with non-GC DLBCL. 1 As with cDNA microarray, immunohistochemistry can also be used to distinguish the GC/non-GC subtype of DLBCL and to predict survival, 2 but there have been few reports comparing clinical outcomes in cases of GC DLBCL and non-GC DLBCL treated with rituximab. 3,4 We retrospectively analyzed the treatment effect of rituximab with conventional chemotherapy on these two DLBCL subtypes by means of immunohistochemistry.…”
Section: Figurementioning
confidence: 99%
“…7,8 Details of the immunohistochemical staining are provided in Table 1. The scoring was based on the algorithm described by Hans et al 2 Bcl-6, CD10 and melanoma associated antigen (mutated) 1 (MUM1) were considered positive if 30% or more of tumor cells were stained with the respective antibody, and bcl-2 was considered positive if 30% or more tumor cells were stained.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…''The JAK2 V617F mutation is detectable in granulocyte populations at greater than two copies per cell among individuals with myeloproliferative disorders'', by El Housni et al Leukemia (2007) 21, 817-818. doi:10.1038/sj.leu.2404569; published online 1 February 2007 In our recent letter to Leukemia, 1 we reported that in lieu of a definitive negative control, or the availability of an alternative 'gold standard' methodology to verify the accuracy of our quantitative assay for the JAK2 V617F mutation, we have used healthy controls as a surrogate to assess assay specificity, and also to establish a clinically useful range for supporting a diagnosis of myeloproliferative disorder.…”
mentioning
confidence: 99%
“…We thank Hammond et al for having provided technical arguments explaining why they consider the finding of mutant JAK2 copies in normal granulocytes as polymerase chain reaction (PCR) artefacts. 1 According to the technical details given, we can understand why the discrimination between the wild-type and mutant JAK2 allele is not absolute as it is only based on the specificity of the 3 0 -end base of a primer. Our methodology is clearly different.…”
mentioning
confidence: 99%